2021
DOI: 10.1038/s41467-021-24064-1
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of HSF1 activity by wildtype p53 creates a driving force for p53 loss-of-heterozygosity

Abstract: The vast majority of human tumors with p53 mutations undergo loss of the remaining wildtype p53 allele (loss-of-heterozygosity, p53LOH). p53LOH has watershed significance in promoting tumor progression. However, driving forces for p53LOH are poorly understood. Here we identify the repressive WTp53–HSF1 axis as one driver of p53LOH. We find that the WTp53 allele in AOM/DSS chemically-induced colorectal tumors (CRC) of p53R248Q/+ mice retains partial activity and represses heat-shock factor 1 (HSF1), the master … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 80 publications
(118 reference statements)
0
17
0
Order By: Relevance
“…An algorithm-based study predicts the presence of p53-responsive elements in the human DNAJA1/HDJ2's promoter, which is confirmed by chromatin-immunoprecipitation studies using MCF7 cells (wtp53) [77]. Moreover, a recent report shows that wtp53 indirectly represses mRNA expression of DNAJA1/HDJ2 by inhibiting phosphorylation of heat-shock factor 1 (HSF1), the master regulator of the proteotoxic stress response [78]. However, DNAJA1/HDJ2 levels are unchanged following exogenous introduction of wtp53 in mutp53-knockout HN31 cells [65].…”
Section: Dnajb1/hdj1mentioning
confidence: 76%
“…An algorithm-based study predicts the presence of p53-responsive elements in the human DNAJA1/HDJ2's promoter, which is confirmed by chromatin-immunoprecipitation studies using MCF7 cells (wtp53) [77]. Moreover, a recent report shows that wtp53 indirectly represses mRNA expression of DNAJA1/HDJ2 by inhibiting phosphorylation of heat-shock factor 1 (HSF1), the master regulator of the proteotoxic stress response [78]. However, DNAJA1/HDJ2 levels are unchanged following exogenous introduction of wtp53 in mutp53-knockout HN31 cells [65].…”
Section: Dnajb1/hdj1mentioning
confidence: 76%
“…Previous studies have reported that constitutively active HSF1 in pancreatic islet cells enhances glucose‐induced insulin secretion, 9,12,13 but their specific contribution to insulin action still needs to be explored. Moreover, HSF1 regulates several non‐heat shock protein genes that support oncogenic processes, including cell cycle regulation, signaling, metabolism, adhesion, and translation 14–18 . Skeletal muscles are the main site of insulin‐stimulated glucose utilization; however, it is unclear whether and how muscle HSF1 affects glucose metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, HSF1 regulates several non-heat shock protein genes that support oncogenic processes, including cell cycle regulation, signaling, metabolism, adhesion, and translation. [14][15][16][17][18] Skeletal muscles are the main site of insulin-stimulated glucose utilization; however, it is unclear whether and how muscle HSF1 affects glucose metabolism. In the present study, we investigated the role of HSF1 in muscle glucose metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Among the mechanisms that result in increased levels of nuclear HSF1, in a broad range of cancers, include amplification of the HSF1 gene located within chromosome 8q24.3, reduced expression of the HSF1 degradation F box E3 ligase Fbxw7, activation by loss of p53 and increased HSF1 transcription by oncogenic signaling pathways such as NOTCH signaling 30 , 80 82 . Other potential contributing factors are the accumulation of the mutant cancer proteome and rapid proliferation of cancer cells, which may select for increased levels and activity of HSF1 via additional mechanisms.…”
Section: Discussionmentioning
confidence: 99%